2018
DOI: 10.1111/pbi.12986
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐made E2 glycoprotein single‐dose vaccine protects pigs against classical swine fever

Abstract: Classical Swine Fever Virus (CSFV) causes classical swine fever, a highly contagious hemorrhagic fever affecting both feral and domesticated pigs. Outbreaks of CSF in Europe, Asia, Africa and South America had significant adverse impacts on animal health, food security and the pig industry. The disease is generally contained by prevention of exposure through import restrictions (e.g. banning import of live pigs and pork products), localized vaccination programmes and culling of infected or at-risk animals, oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 43 publications
4
35
0
Order By: Relevance
“…The expected size of the E2 recombinant protein is 64 kD; therefore, the strong band appeared to be larger than expected. We assume that this is due to N-glycosylation since E2 protein has putative 7 N-glycosylation sites (Laughlin et al 2019). Consistent with this, previous studies reported that CBD-fused E2 recombinant proteins have several N-glycosylation sites and are larger than expected when expressed in plants (Park et al 2019;Sohn et al 2018).…”
Section: Generation Of the Pme2:pfc2 Fusion Construct And Protein Expsupporting
confidence: 82%
See 1 more Smart Citation
“…The expected size of the E2 recombinant protein is 64 kD; therefore, the strong band appeared to be larger than expected. We assume that this is due to N-glycosylation since E2 protein has putative 7 N-glycosylation sites (Laughlin et al 2019). Consistent with this, previous studies reported that CBD-fused E2 recombinant proteins have several N-glycosylation sites and are larger than expected when expressed in plants (Park et al 2019;Sohn et al 2018).…”
Section: Generation Of the Pme2:pfc2 Fusion Construct And Protein Expsupporting
confidence: 82%
“…In addition, Arabidopsis thaliana-derived E2 antibodies in a mouse can recognize the native E2 protein suggesting that structure of plant-produced E2 is comparable to native E2 protein (Sohn et al 2018). In addition, transient expression of recombinant E2 protein from the leaves of Nicotiana benthamiana or from the leaves of transgenic N. benthamiana lines generates antibodies that can neutralize CSFV in pigs and protect them against subsequent challenge with CSFV (Laughlin et al 2019;Park et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that as cELISA proved to be nearly as sensitive and specific as the VNT while being simpler and more rapid, it would be an adequate screening test for CDV or PDV cases [23]. The glycoprotein E2 exposed on the outer surface of CSFV is the major immuno-protective antigen of C-strain vaccine that is responsible for inducing neutralizing antibodies and eliciting protective immunity against CSFV [13][14][15][16][17][18][19][20]. Thus, it is not surprising that E2 protein has been successfully used to develop ELISAs to measure anti-CSFV antibody response in pigs after vaccination [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Virus neutralization test (VNT) is considered as the gold standard for serological monitoring and efficacy evaluation of CSF vaccines. However, it has several limitations including time-consuming, requirement of cell culture, the need for live virus manipulation, and relatively expensive [2,[18][19][20][21]. Here, we described a competitive ELISA (cELISA) developed with a neutralizing anti-E2 monoclonal antibody.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we developed a neutralizing mAb based cELISA with the emphasis on the replacement of and specific as the VNT while being simpler and more rapid, it would be an adequate screening test for CDV or PDV cases [23]. The glycoprotein E2 exposed on the outer surface of CSFV is the major immuno-protective antigen of C-strain vaccine that is responsible for inducing neutralizing antibodies and eliciting protective immunity against CSFV [13][14][15][16][17][18][19][20]. Thus, it is not surprising that E2 protein has been successfully used to develop ELISAs to measure anti-CSFV antibody response in pigs after vaccination [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%